2023
DOI: 10.1039/d3ta01778h
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the solubility of Mn in AgSbSe2 for high thermoelectric performance through entropy engineering

Zheng Ma,
Yubo Luo,
Wang Li
et al.

Abstract: Point defects play an import role in regulating the electrical and thermal transport properties of thermoelectric materials, but it always restricted by the solubility of dopant in the matrix. Herein,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…234 Roychowdhury et al applied the entropy-driven concept for a GeSe-based material, and the reported ZT for (GeSe) 0.5 (AgBiSe 2 ) 0.5 was found to be 0.45 at 677 K. 235 The incorporation of AgBiSe into the GeSe portion resulted in a transition of the material's conductivity from the p- to the n-type, leading to a substantial increase in the carrier concentration from 1.2 × 10 17 cm −3 recorded for the pure GeSe compound to 3.29 × 10 18 cm −3 . 235 Ma et al 236 applied the entropy-driven concept to increase the solubility of Mn in AgSbSe 2 , increasing it from 8% to 30% by utilizing the entropy-driven concept by alloying with MnSe. They found a remarkable ZT value of 0.96 and 1.18 at 750 K for (AgSbSe 2 ) 0.7 (MnSe) 0.3 (Fig.…”
Section: Overview Of High-entropy Thermoelectric Materialsmentioning
confidence: 99%
“…234 Roychowdhury et al applied the entropy-driven concept for a GeSe-based material, and the reported ZT for (GeSe) 0.5 (AgBiSe 2 ) 0.5 was found to be 0.45 at 677 K. 235 The incorporation of AgBiSe into the GeSe portion resulted in a transition of the material's conductivity from the p- to the n-type, leading to a substantial increase in the carrier concentration from 1.2 × 10 17 cm −3 recorded for the pure GeSe compound to 3.29 × 10 18 cm −3 . 235 Ma et al 236 applied the entropy-driven concept to increase the solubility of Mn in AgSbSe 2 , increasing it from 8% to 30% by utilizing the entropy-driven concept by alloying with MnSe. They found a remarkable ZT value of 0.96 and 1.18 at 750 K for (AgSbSe 2 ) 0.7 (MnSe) 0.3 (Fig.…”
Section: Overview Of High-entropy Thermoelectric Materialsmentioning
confidence: 99%